The flexibility of SABRE, a new quantitative receptor function model, when fitting challenging concentration-effect data - Olah, Barbara; Tarjanyi, Vera; Takacs, Barbara; Pluzsnyik, Edua; Viczjan, Gabor; Ovari, Ignac; Szilvassy, Zoltan; Juhasz, Bela; Zsuga, Judit; Erdei, Tamas; Gesztelyi, Rudolf (Frontiers in Pharmacology, 2025)
The Signal Amplification, Binding affinity, and Receptor-activation Efficacy (SABRE) model is the most recent general and quantitative model of receptor function, which enables the determination of Kd (the equilibrium dissociation constant of the agonist-receptor complex) and q (the fraction of the operable receptors after a partial irreversible receptor inactivation) from purely functional data. The practical aim of the present study was to test the capabilities of this new model using concentration-effect (E/c) data from a previous investigation conducted in our laboratory. We have found that the SABRE model is at least as useful as two widely accepted older methods thought to have similar capabilities, the operational model of agonism and Furchgott’s method, even if the quality of the data to be evaluated is somewhat challenging. Nevertheless, the SABRE model seems to require a large amount of high-quality and, regarding the experimental design, diverse data. In addition, it is important to find the most suitable fitting strategy for the particular sort of data in order to obtain reliable results. However, owing to its unique feature of distinguishing between receptor activation and activation of postreceptorial signaling, the SABRE model appears to be superior to previous quantitative receptor function models in simulating E/c curves and thereby clarifying, explaining or simply illustrating theoretical issues.